Application of equilibrium passive sampling to profile pore water and accessible concentrations of hydrophobic organic contaminants in Danube sediments. (December 2020) - Belháčová-Minaříková, Michaela; Smedes, Foppe; Rusina, Tatsiana P.; Vrana, Branislav
Abstract: Total concentrations of hydrophobic organic contaminants (HOCs) in sediment present a poor quality assessment parameter for aquatic organism exposure and environmental risk because they do not reflect contaminant bioavailability. The bioavailability issue of HOCs in sediments can be addressed by application of multi-ratio equilibrium passive sampling (EPS). In this study, riverbed sediment samples were collected during the Joint Danube Survey at 9 locations along the Danube River in 2013. Samples were ex-situ equilibrated with silicone passive samplers. Desorption isotherms were constructed, yielding two endpoints: pore water ( C W:0 ) and accessible ( C AS:0 ) concentration of polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs), polycyclic aromatic hydrocarbons (PAHs) and polybrominated diphenyl ethers in sediment. C W:0 concentrations of DDT and its breakdown products exhibited elevated levels in the low Danube, with the maximum in the river delta. Other investigated HOCs did not show any clear spatial trends along the river, and only a moderate C W:0 variability. C AS:0 in sediment ranged from 10 to 90% of the total concentration in sediment. C W:0 was compared with freely dissolved concentration in the overlaying surface water, measured likewise by passive sampling. The comparison indicated potential compound release from sediment to the water phase for PAHs with less than four aromatic rings, and for remaining HOCs either equilibrium between sediment and water, or potential compound deposition in sediment. Sorption partition coefficients of HOC to organic carbon correlated well with octanol-water partition coefficients ( K OW ), showing stronger sorption of PAHs to sediment than that of PCBs and OCPs having equal log K OW . Comparison of C W:0 values with European environmental quality standards indicated potential exceedance for hexachlorobenzene, fluoranthene and benzo[ a ]pyrene at several sites. The study demonstrates the utility of passive sampling as an innovative approach for risk-oriented monitoring of HOCs in river catchments. Graphical abstract: Image 1 Highlights: Equilibrium passive sampling characterized sorption of organics to Danube sediments. Sediment pore water concentrations were in the same range as in the surface water. K OC for the accessible contaminant fraction correlated well with K OW. Lower accessibility in sediment was for compounds with planar molecules.